Pengaruh Tax Planning, Nilai Perusahaan, Dan Leverage Terhadap Manajemen Laba Padaperusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2016-2019 - Trisma Wati; Sam’ani Sam’ani (Jurnal Ekonomi Manajemen Akuntansi, 2022)
This study aims to examine the effect of the variables of Tax Planning, Firm Value and Leverage on Earnings Management. In this study, the population is the number of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange from 2016-2019 which amounted to 28 companies with sampling carried out using a non-probability sampling approach with a sampling technique using purposive sampling. Purposive sampling is a sampling technique with certain considerations. So the number of samples that meet the criteria is 13 companies multiplied by 4 years to 52 samples. The results of the study using the F test showed that the calculated F value was 4.441 > F table = 2.88 with a significance level of 0.010 <0.05. So it can be concluded that the model is a fit model. The results of the t-test value of t-count Tax planning (X1) is -2.453 < t table of 2.03452 and the probability value is less than 0.05, which is 0.020. This shows that the Tax Planning (X1) variable has a significant effect on Earnings Management with a negative direction or relationship. The t-count value The firm value (X2) is 2.550 > t table is 2.03452 and the probability value is less than 0.05, which is 0.016. This shows that the Firm Value variable (X2) has a significant positive effect on Earnings Management. The t-count value of Leverage (X3) is 1.556 < t table of 2.03452 and the probability value is greater than 0.05, which is 0.129. This shows that the Leverage (X3) variable has no effect on Earnings Management.